Peranan Guru Bimbingan dan Konseling dalam Meningkatkan Perilaku Prososial Siswa Pada Pembelajaran Daring - Sri Utami; Rezky Permata Sari; Dian Renata (Guidance : Jurnal Bimbingan dan Konseling, 2021)
Prosocial behavior needs to be developed in everyday life by students, including online learning activities. In fact, there were still students who are still unable to behave prosocially in online learning. The role of Guidance and Counseling (BK) teachers is needed as a unit for providing assistance to improve it. This study aims to determine how the role of BK teachers in improving students' prosocial behavior in online learning. This research is a qualitative research with descriptive type. The data in this study were obtained from seven informants, namely principal, vice principal of student affairs, three BK teachers and two students. The five informants are primary data sources. The secondary data obtained through the results of a literature review. Data were collected through interview techniques, observation, and documentation notes. The data were analyzed by componential analysis of the Miles and Huberman model. The data were validated through triangulation technique. The results of the study indicate that the counseling teacher in improving prosocial behavior performs the roles of facilitator, corrector, mediator, and advisor.